Feasibility of intercropping in rabi castor (Ricinus communis L.) - Yadav, B.K.; Patel, G.N.; Choudhary, S.K. (Annals of Agricultural Research, 2019)
An experiment on feasibility of intercropping in rabi castor was conducted at C. P. College of Agriculture, Sardarkrushinagar on loamy sand soil using randomized block design with three replications during 2013-14. Results revealed that rabi castor intercropped with lucerne, carrot, fenugreek and chicory at1:2 row ratio produced significantly higher castor equivalent yield, 3297, 3237, 3057, 2731 and kg/ha respectively over sole castor and other intercrops as sole. Among the intercrops castor + lucerne and castor + chicory found equally effective with respect to castor equivalent yield and found significantly superior over rest of the treatments. While intercropping of castor + fenugreek and castor + lucerne at 1:2 row ratio recorded significantly higher LER (Land equivalent ratio) value than sole crops and other intercropping systems.The maximum net return of ` 75492/ha obtained when castor was intercropped with lucerne followed by castor + carrot and castor + chicory at 1:2 row ratio.The highest benefit cost ratio of 2.33 obtained in castor + lucerne (1:2) followed bycastor + fenugreek and castor + carrot at 1:2 row ratio over other intercropping systems.